From silos to synergy: trainee responses to multidisciplinary training in child and adolescent psychiatry - Usami, Masahide; Mizumoto, Yuki; Itagaki, Kotoe; Yamamoto, Keita; Ohcho, Kozo; Fukuda, Masahiro; Taniguchi, Ayaka; Okuno, Masakage; Tsujii, Noa; Harada, Yuzuru; Nagasawa, Takashi; Saito, Kazuhiko (Frontiers in Psychiatry, 2025)
IntroductionJapan is experiencing a growing demand for child and adolescent mental health services owing to the increasing rates of school refusal, youth suicide, and neurodevelopmental disorders. However, there is a critical shortage of trained professionals as well as limited national efforts to provide multidisciplinary training.MethodsWe evaluated a government-funded training program aimed at enhancing collaboration between clinical, educational, and psychosocial professionals in child psychiatry. A total of 426 participants completed post-training surveys assessing the perceived usefulness of 22 lecture modules (rated 0–10), overall satisfaction (rated 0–10), and open-ended feedback on the curriculum design. An exploratory factor analysis was conducted to identify the latent domains among the modules. Net promoter scores (NPSs) were calculated for each module to gauge the perceived value. Ordinary least-squares regression was used to identify the predictors of overall satisfaction.ResultsFour content domains were identified: foundational knowledge, therapeutic skills, problem behavior management, and multidisciplinary collaboration. The mean satisfaction score was 4.6/5. The modules with the highest NPS were team-based care and practical case-based learning. Participants with educational and psychosocial roles reported significantly higher satisfaction than clinical staff. The regression analysis revealed that therapeutic skills and collaboration were significant predictors of overall satisfaction.ConclusionMultidisciplinary training programs are feasible and well-received in Japan. The participants prioritized interactive, role-based learning and emphasized the need for content tailored to real-world teamwork. These findings could inform future curriculum development and workforce policies in child and adolescent psychiatry.